Creativity as a respite during COVID-19: A Study on selected Psychological Factors - Anupriya Naruka, Dr. Chirmi Acharya, Dr. Tarika Sharma, Dr. Manisha Tiwari, Dr. Vishakha Saini (South Eastern European Journal of Public Health, 2025)
Creativity is not only encompassed by the artists and scientists, as it is not limited to art and creation but it goes deeper. As everybody encompasses creativity as we use it now and then in the form of critical thinking, problem-solving, and meeting up a deadline or dealing with everyday challenges. With people being cooped up in their homes, level of one’s creativity impacted happiness, coping, meaning-making, and stress during the challenging phase of COVID-19. This paper aimed to study the role of creativity in impacting happiness, coping, meaning-making, and stress during the pandemic among college students. The data was collected online from 371 college students of various universities and colleges in the city of Jaipur, India. The findings suggest that creativity tend to enhance happiness and meaning-making among the population, by enhancing the coping strategies of an individual. It was also found that stress tend to decrease when one engages in creativity and creative tasks even in the situation of challenge and panic.